Critical Reading Profile: Analysis Of Literacy Skills And Habits Of The Kasepuhan Banten Kidul Community - Eka Nurul Mualimah; Vismaia S. Damayanti; Andoyo Sastromiharjo; Yeti Mulyati (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study aims to examine the profile of critical reading, including reading habits, critical reading skills, and reading activities of the Kasepuhan Banten Kidul community. Critical reading skills are an essential foundation for modern society, which requires not only understanding the content of information but also evaluating the accuracy, relevance, and credibility of the sources of information obtained. Research on critical reading in indigenous communities especially studies that integrate reading habits, skills, and activities simultaneously using a mixed-methods approach remains limited. This study employs a mixed-methods design, with a qualitative approach used to explore the community's experiences, practices, and perceptions related to critical reading activities, while the quantitative approach measures reading frequency and comprehension levels. The study involved 279 participants, using data collection instruments including a 34-item reading habits questionnaire, a reading comprehension test analyzing 3 news items, and observations of reading activities. The results indicate that reading habits were at a moderate level for 217 respondents (77.8%), while critical reading skills were low, with 119 respondents scoring between 50–59. Pre-reading attention was relatively good, with most respondents paying attention to the title before reading the text (205 of 279 respondents) and also to images or illustrations accompanying the text (218 respondents). These findings suggest that reading activities have not been fully accompanied by deep cognitive engagement or a critical attitude toward content and sources.